A supernumerary designer chromosome for modular in vivo pathway assembly in Saccharomyces cerevisiae. Issue 3 (11th January 2021) - Postma, Eline D; Dashko, Sofia; van Breemen, Lars; Taylor Parkins, Shannara K; van den Broek, Marcel; Daran, Jean-Marc; Daran-Lapujade, Pascale
Abstract: The construction of microbial cell factories for sustainable production of chemicals and pharmaceuticals requires extensive genome engineering. Using Saccharomyces cerevisiae, this study proposes synthetic neochromosomes as orthogonal expression platforms for rewiring native cellular processes and implementing new functionalities. Capitalizing the powerful homologous recombination capability of S. cerevisiae, modular neochromosomes of 50 and 100 kb were fully assembled de novo from up to 44 transcriptional-unit-sized fragments in a single transformation. These assemblies were remarkably efficient and faithful to their in silico design. Neochromosomes made of non-coding DNA were stably replicated and segregated irrespective of their size without affecting the physiology of their host. These non-coding neochromosomes were successfully used as landing pad and as exclusive expression platform for the essential glycolytic pathway. This work pushes the limit of DNA assembly in S. cerevisiae and paves the way for de novo designer chromosomes as modular genome engineering platforms in S. cerevisiae .